PENGARUH VARIABEL EKONOMI MAKRO TERHADAP PEMBIAYAAN PERBANKAN SYARIAH PERIODE 2010-2018 - Jie Novita (Jurnal Ekonomi dan Bisnis, 2020)
The purpose of the research is to examine and analyze the effect of macroeconomic variables GDP and inflation on Islamic banking financing in Indonesian. Islamic bank financing is the dependent variable, whereas GDP, reference interest rates, and inflation are the independent variable. The data used is Islamic banking financing, GDP, reference interest rates, and inflation in Indonesian from 2010-1018. This empirical study uses a quantitative approach and method of OLS (Ordinary Least Square). The results of this research indicate that the GDP variable has positive and statistically significant effect on Islamic banking financing, the variable reference interest rates (BI Rate and BI Rate 7days Repo Rate) have negative and statistically significant effect on Islamic banking financing, the inflation variable has positive and statistically significant effect on Islamic banking financing.